ChemInform Abstract: The Orthoperiodates of Calcium, Strontium, and Barium. Issue 19 (May 2015) - Hummel, Thorsten; Salk, Florian; Stroebele, Markus; Enseling, David; Juestel, Thomas; Meyer, H.‐Juergen
Abstract: M5 (IO6 )2 (M: Ca, Sr, Ba) are prepared by solid‐state reactions of metal iodides or metal iodates in air.